PELEBELAN TOTAL TITIK AJAIB PADA GRAF ANTIPRISMA - Noho, Andi D; Ismail, Sumarno (Universitas Negeri Surabaya, 2024)
G was a graph with a set of vertices and a set of edges Graph Labeling was a mapping or function that paired every part of the graph (vertices, edges, or both) with a positive integer. A total vertex labeling on the graph was a bijective mapping from to the set of integer numbers in such a way that there was a positive integer k that satisfied for every . The research findings indicated that for the antiprism graph , it had a magic constant of . for odd n where Keywords: Magic Constant Number, Antiprism Graph, Magic Vertex Total Labeling